1999
DOI: 10.1046/j.1365-2044.1999.00668.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and pharmacokinetics of 1% ropivacaine and 0.75% bupivacaine in peribulbar anaesthesia for cataract surgery

Abstract: SummaryPeribulbar anaesthesia with 1% ropivacaine and 0.75% bupivacaine, both with hyaluronidase, was assessed in a prospective, randomised, double-blind study of 100 patients undergoing cataract surgery. Pharmacokinetic data were obtained from 22 subjects. Akinesia of the globe developed slightly more rapidly in the ropivacaine group, but this difference was only statistically significant at 2 min after injection of the local anaesthetic. Lid akinesia was significantly more complete in the ropivacaine group. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 25 publications
1
22
0
2
Order By: Relevance
“…Similar results with 1% ropivacaine concentration have been reported by Huha et al 10 who demonstrated an 80% frequency of complete akinesia 10 minutes after injecting 8 mL of local anesthetic solution. In a previous investigation comparing ropivacaine and a lidocaine-bupivacaine mixture for vitreoretinal surgery, we observed a 10 Ϯ 5 minute onset time of motor block with 0.75% ropivacaine.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar results with 1% ropivacaine concentration have been reported by Huha et al 10 who demonstrated an 80% frequency of complete akinesia 10 minutes after injecting 8 mL of local anesthetic solution. In a previous investigation comparing ropivacaine and a lidocaine-bupivacaine mixture for vitreoretinal surgery, we observed a 10 Ϯ 5 minute onset time of motor block with 0.75% ropivacaine.…”
Section: Discussionsupporting
confidence: 88%
“…10 We wished to detect a 30% difference in the frequency of globe akinesia 15 minutes after completing the injection between different ropivacaine concentrations, accepting a two-tailed ␣ error of 5% and a ␤ error of 20%. 11 Based on these calculations, the required study size was 21 patients per group.…”
Section: Methodsmentioning
confidence: 99%
“…This finding is similar to reduction in IOP when used in peribulbar block. [10,13,14] In a study by Nociti JR, despite similar blockade with analgesia and akinesia 1% ropivacaine decreased the intraocular pressure immediately after its administration, unlike 0.75% bupivacaine which promoted an initial elevation in intraocular pressure followed by a reduction. The authors suggested that the difference could be due to the vasoconstrictive action of ropivacaine.…”
Section: Discussionmentioning
confidence: 97%
“…It has been suggested that in peribulbar anaesthesia, the differences in the potency of the motor blockade between both anaesthetics could be concentrationdependent. [10] Comparison of different concentrations of ropivacaine in 68 patients showed that the concentration of 0.75% is preferable to 0.5% and 1.0%, which produce respectively lower akinesia and prolonged anaesthetic recovery. [4] In a study that compared peribulbar ropivacaine, racemic bupivacaine and levobupivacaine, all in concentrations of 0.75%.…”
Section: Discussionmentioning
confidence: 99%
“…13 D. K. Woodward and A. T. S. Leung et al studied peribulbar anaesthesia with 1% ropivacaine and hyaluronidase 300 IU mL -1 : in comparison with 0.5% bupivacaine, 2% lidocaine and hyaluronidase 50 IU/mL. They showed no difference in the rate of onset and degree of akinesia achieved.…”
Section: Discussionmentioning
confidence: 99%